Fine-Mapping and Analysis of Cgl1, a Gene Conferring Glossy Trait in Cabbage (Brassica oleracea L. var. capitata) - Liu, Zezhou; Fang, Zhiyuan; Zhuang, Mu; Zhang, Yangyong; Lv, Honghao; Liu, Yumei; Li, Zhansheng; Sun, Peitian; Tang, Jun; Liu, Dongming; Zhang, Zhenxian; Yang, Limei (Frontiers in Plant Science, 2017)
Cuticular waxes covering the outer plant surface impart a whitish appearance. Wax-less cabbage mutant shows glossy in leaf surface and plays important roles in riching cabbage germplasm resources and breeding brilliant green cabbage. This is the first report describing the characterization and fine-mapping of a wax biosynthesis gene using a novel glossy Brassica oleracea mutant. In the present paper, we identified a glossy cabbage mutant (line10Q-961) with a brilliant green phenotype. Genetic analyses indicated that the glossy trait was controlled by a single recessive gene. Preliminary mapping results using an F2 population containing 189 recessive individuals revealed that the Cgl1 gene was located at the end of chromosome C08. Several new markers closely linked to the target gene were designed according to the cabbage reference genome sequence. Another population of 1,172 recessive F2 individuals was used to ?ne-map the Cgl1 gene to a 188.7-kb interval between the C08SSR61 simple sequence repeat marker and the end of chromosome C08. There were 33 genes located in this region. According to gene annotation and homology analyses, the Bol018504 gene, which is a homolog of CER1 in Arabidopsis thaliana, was the most likely candidate for the Cgl1 gene. Its coding and promoter regions were sequenced, which indicated that the RNA splice site was altered because of a 2,722-bp insertion in the first intron of Bol018504 in the glossy mutant. Based on the FGENESH 2.6 prediction and sequence alignments, the PLN02869 domain, which controls fatty aldehyde decarbonylase activity, was absent from the Bol018504 gene of the 10Q-961 glossy mutant. We inferred that the inserted sequence in Bol018504 may result in the glossy cabbage mutant. This study represents the first step toward the characterization of cuticular wax biosynthesis in B. oleracea, and may contribute to the breeding of new cabbage varieties exhibiting a brilliant green phenotype.